Improving the Efficiency and Equity of Public Education Spending : The Case of Moldova - Jin, Hui (IMF Working Papers; Working Paper ;, 2019)
This paper, using Moldova as an example, presents a systematic approach to assess the efficiency and equity of public education spending, identify sources of inefficiencies and inequality, and formulate potential reform options. The analytical framework combines international benchmarking with country-specific analysis-such as microeconomic analysis based on household survey data-and can provide important insights into diagnosing and reforming education systems. The analysis finds significant scope to improve both efficiency and equity of the education sector in Moldova. Potential reform measures include further consolidating the oversized school network, reducing overstaffing, and better targeting government subsidies. The current remuneration policy could also be improved to attract high quality teachers and incentivize performance.